2021
DOI: 10.1002/leap.1345
|View full text |Cite
|
Sign up to set email alerts
|

Investigating gender differences in journal selection decisions: A survey of academic researchers

Abstract: This article examines the impact of gender on researchers' journal selection decisions, and thereby seeks to contribute to previous research on the impact of gender on academics' career progression and publishing performance. Prior research suggests that female academics suffer from lower levels of career progression and publishing than male academics. Research suggests various explicit factors that might influence this scenario, including bias in hiring, choice of discipline, and under‐representation of women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…They suggested while both genders agree on the importance of some factors, it is also evident that women are more alert to issues of authority, expectations placed on them regarding publishing high-quality articles and career progression than are men. Men prioritize familiarity, experience and speed more highly than women (Rowley and Sbaffi, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested while both genders agree on the importance of some factors, it is also evident that women are more alert to issues of authority, expectations placed on them regarding publishing high-quality articles and career progression than are men. Men prioritize familiarity, experience and speed more highly than women (Rowley and Sbaffi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that there was no significant difference between the "attitudes and beliefs towards journal selection" as well as "familiarity with journal metrics" based on gender. The results are inconsistent with the results found by Rowley and Sbaffi (2020). They suggested while both genders agree on the importance of some factors, it is also evident that women are more alert to issues of authority, expectations placed on them regarding publishing high-quality articles and career progression than are men.…”
Section: Discussionmentioning
confidence: 99%
“…We do not analyse gender. Gender influences what researchers choose to study, how they approach the publication process, and how they are treated within the publication process (Rowley & Sbaffi, 2021). However, during the study period, ISJ did not collect information on gender, and we cannot completely collect this information after the fact.…”
Section: Methodsmentioning
confidence: 99%